P-116 'Shocking' communication skills – communication skills training for cardiac physiologists deactivating ICDS. (1st March 2017) - Curtis, Matthew; Evans, Sioned; Clayton, Benjamin
Abstract : Background: Studies have highlighted a strikingly low rate of preparatory conversations regarding the deactivation of patients' implantable cardiac defibrillators (ICDs) at the end of life. Rates of implantation of ICDs have increased, indicating that managing ICDs at the end of life will become a more common occurrence. Cardiac Physiologists carry out the deactivation of ICDs, yet locally in Devon, Cardiac Physiologists have highlighted that they have no training of how to communicate with patients when deactivating their ICDs. Aims: To improve end of life communication skills for Cardiac Physiologists. Methods: A joint educational programme was developed to improve end of life communication skills for Cardiac Physiologists and increase the ICD-related knowledge base of Palliative Care teams. Interactive role-play sessions were developed based on examples of challenging or common communication scenarios provided by the Cardiac Physiologists prior to the session. Feedback was collected immediately after the session and then 4 months later to assess the impact on their actual practice. Results: Immediate feedback stated the training had been very useful. Further results regarding how well the Physiologists have put the learning into practice will be available in the near future. The majority of Palliative Care attendees admitted to little understanding of cardiac devices before the study day compared to a good understanding afterwards. Conclusions: Cardiac Physiologists are a group of the non-cancer workforce who are potentially neglected with regards to end of life communication skills training. We would encourage other services around the country to provide this training to improve the end of life care for patients with ICDs. Interactive role play appears to have been a successful method to provide this training. The joint educational programme between Cardiology and Palliative Care facilitated learning from shared differing experiences and helped develop relationships between the teams.